Hypolipidemic mechanism of Pleurotus eryngii polysaccharides in high-fat diet-induced obese mice based on metabolomics - Zhao, Yuanyuan; Zhang, Zhen; Wang, Li; Li, Wen; Du, Jianming; Zhang, Shengxiang; Chen, Xuefeng (Frontiers in Nutrition, 2023)
Objective In this study, the structure of Pleurotus eryngii polysaccharides (PEPs) was characterized, and the mechanism of PEP on obesity and hyperlipidemia induced by high-fat diet was evaluated by metabonomic analysis. Methods The structure of PEPs were characterized by monosaccharide composition, Fourier transform infrared spectroscopy and thermogravimetry. In animal experiments, H&E staining was used to observe the morphological difference of epididymal adipose tissue of mice in each group. Ultrahigh performance liquid chromatography (UHPLC)-(QE) HFX -mass spectrometry (MS) was used to analyze the difference of metabolites in serum of mice in each group and the related metabolic pathways. Results The PEPs contained nine monosaccharides: 1.05% fucose, 0.30% arabinose, 17.94% galactose, 53.49% glucose, 1.24% xylose, 23.32% mannose, 1.30% ribose, 0.21%galacturonic acid, and 1.17% glucuronic acid. The PEPs began to degrade at 251°C (T0), while the maximum thermal degradation rate temperature (Tm) appeared at 300°C. The results histopathological observation demonstrated that the PEPs had signifificant hypolipidemic activities. After PEPs intervention, the metabolic profile of mice changed significantly. A total of 29 different metabolites were selected as adjunctive therapy to PEPs, for treatment of obesity and hyperlipidemia-related complications caused by a high-fat diet. These metabolites include amino acids, unsaturated fatty acids, choline, glycerol phospholipids, and other endogenous compounds, which can prevent and treat obesity and hyperlipidemia caused by a high-fat diet by regulating amino acid metabolism, fatty acid metabolism, and changes in metabolic pathways such as that involved in the citric cycle (TCA cycle). Conclusions The presented results indicate that PEPs treatment can alleviate the obesity and hyperlipidemia caused by a high-fat diet and, thus, may be used as a functional food adjuvant, providing a theoretical basis and technical guidance for the prevention and treatment of high-fat diet-induced obesity and hyperlipidemia.